Production of picosecond, kilojoule, and petawatt laser pulses via Raman amplification of nanosecond pulses - Trines, R; Fiúza, F; Bingham, R; Fonseca, R; Silva, L; Cairns, R; Norreys, P (2011)
Raman amplification in plasma has been promoted as a means of compressing picosecond optical laser pulses to femtosecond duration to explore the intensity frontier. Here we show for the first time that it can be used, with equal success, to compress laser pulses from nanosecond to picosecond duration. Simulations show up to 60% energy transfer from pump pulse to probe pulse, implying that multikilojoule ultraviolet petawatt laser pulses can be produced using this scheme. This has important consequences for the demonstration of fast-ignition inertial confinement fusion. © 2011 American Physical Society.